Contribution of Self-Concept and Learning Independence to the Resilience of Students in Open University - Barokah Widuroyekti; Inneke Putri Widyani; Jahju Hartanti; Lindsay N Bergsma (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to examine cross-sectionally the correlation between self-concept and self-reliance to the resilience ability of the Distance Learning Program Unit-Open University students. Method: The method used is correlational with the quantitative approach with its measurement instrument using a questionnaire. The data analysis used is correlation analysis with parametric statistics. Results: The results of this study show that the three variables have a significant positive correlation. The categories of self-concept and self-reliance of students are in the high category, while their resilience ability is in the medium category. Novelty: Researchers hope this research will continue, so the following suggestion for the following researchers is to develop an approach in guidance and counseling to improve self-reliance and student resilience in remote lectures.